Survey of Elementary School Students' Understanding of Traditional Games in the Kertosono Area - Meilia Karonia; Rizki Burstiando; Muhammad Yanuar Rizky (CV. Nusantara Sporta, 2024)
This research is motivated by the author's observation in the area where he lives that traditional games are now rarely played. More interest in other games makes students less interested in traditional games. As a result, students' understanding of traditional games is decreasing and the existence of traditional games among students is decreasing. The aim of this research was to determine the level of understanding of 5th grade elementary school students in the Kertosono area regarding traditional games. This type of research is quantitative descriptive using survey methods. The instrument used is a questionnaire or questionnaire. The subjects of this research were 4 grade 5 elementary school students in the Kertosono area, namely from SDN Banaran 1, SDN Banaran 2, SDN Kudu 1, and SDN Kudu 2 with a total of 120 students. The results of this research indicate that students' understanding of traditional games is mostly in the Medium category. This can be proven by data on the number of students with High understanding of 34 students or 28%, students with Moderate understanding of 67 students or 56%, and students with Low understanding of 19 students or 16%.